Expression of intronic miRNAs and their host gene Igf2 in a murine unilateral ureteral obstruction model - Li,N.Q. (2015)
The objective of this study was to determine the expression of miR-483 and miR-483* and the relationship among them, their host gene (Igf2), and other cytokines in a murine model of renal fibrosis. The extent of renal fibrosis was visualized using Masson staining, and fibrosis was scored 3 days and 1 and 2 weeks after unilateral ureteral obstruction (UUO). Expression of miR-483, miR-483* and various cytokine mRNAs was detected by real-time polymerase chain reaction (PCR). Expression of miR-483 and miR-483* was significantly upregulated in the UUO model, particularly miR-483 expression was the greatest 2 weeks after surgery. Additionally, miR-483 and miR-483* expression negatively correlated with Bmp7 expression and positively correlated with Igf2, Tgfβ, Hgf, and Ctgf expression, as determined by Pearson's correlation analysis. Hgf expression significantly increased at 1 and 2 weeks after the surgery compared to the control group. This study showed that miR-483 and miR-483* expression was upregulated in a murine UUO model. These data suggest that miR-483 and miR-483* play a role in renal fibrosis and that miR-483* may interact with miR-483 in renal fibrosis. Thus, these miRNAs may play a role in the pathogenesis of renal fibrosis and coexpression of their host gene Igf2.